Intelligent voice control system for UAV with mobile robot - Atanov, Sabyrzhan; Moldamurat, Khuralay; Bakyt, Makhabbat; Zinagabdenova, Dariga; Moldamurat, Aibek; Zhumazhanov, Berik; Maidanov, Adil (Indonesian Journal of Electrical Engineering and Computer Science, 2025)
The article presents a voice control system for unmanned aerial vehicles (UAVs) and an integrated mobile robot, based on artificial intelligence (AI). The system recognizes voice commands in the Kazakh language, converted into Latin transliteration, providing intuitive control of the UAV and robot. The performance of the system in various scenarios including agriculture, environmental monitoring and search and rescue operations is investigated. The system showed high accuracy of command recognition (95%) and efficient control of the UAV and robot. The proposed system opens up new possibilities for the use of UAVs and robots in various fields, increasing their autonomy, flexibility and ease of use.